Phase-stable, multi-µJ femtosecond pulses from a repetition-rate tunable Ti:Sa-oscillator-seeded Yb-fiber amplifier - Saule, T.; Holzberger, S.; De Vries, O.; Ploetner, M.; Limpert, Jens; Tuennermann, A.; Pupeza, I. (Applied Physics B-Lasers and Optics, 2017)
We present a high-power, MHz-repetition-rate, phase-stable femtosecond laser system based on a phase-stabilized Ti:Sa oscillator and a multi-stage Yb-fiber chirped-pulse power amplifier. A 10-nm band around 1030 nm is split from the 7-fs oscillator output and serves as the seed for subsequent amplification by 54 dB to 80 W of average power. The µJ-level output is spectrally broadened in a solid-core fiber and compressed to 30 fs with chirped mirrors. A pulse picker prior to power amplification allows for decreasing the repetition rate from 74 MHz by a factor of up to 4 without affecting the pulse parameters. To compensate for phase jitter added by the amplifier to the feed-forward phase-stabilized seeding pulses, a self-referencing feed-back loop is implemented at the system output. An integrated out-of-loop phase noise of less than 100 mrad was measured in the band from 0.4 Hz to 400 kHz, which to the best of our knowledge corresponds to the highest phase stability ever demonstrated for high-power, multi-MHz-repetition-rate ultrafast lasers. This system will enable experiments in attosecond physics at unprecedented repetition rates, it offers ideal prerequisites for the generation and field-resolved electro-optical sampling of high-power, broadband infrared pulses, and it is suitable for phase-stable white light generation.
CRIS-Team Scopus Importer:2023-04-20